(untitled) (Fiep Bulletin - online, 2013)
This study started from the observation of how School Physical Education has been worked and its possible contributions in students’ lives and formation. The objective was to verify students´ expectations on this discipline, which is part of school curriculum, and the possible influences such expectations could generate. The study was characterized as a descriptive research, defined by Cervo and Bervian (1996) as a research that observes, registers, analyzes facts or phenomena without manipulating them. Data collection was made in four state schools located in the first district of the city of Duque de Caxias. The questionnaire was compound by open questions. Contested to the questionnaire two hundred (200) students from the seventh (7th) year of schooling in state´s public school system. The conclusion about that expectation was linked to the learning of sports´ modalities as a way to a possible social rising. It can lead to the interpretation that there is a reductionist tendency among professionals from Physical Education area, who limit their performance to a simple recreation or sport practicing, not considering the social function of School Physical Education inside teaching institutions, creating in the student a difficulty to comprehend about possible expectations that could be achieved through School Physical Education classes. We understand that this panorama could only be modified if there is a consolidation of School Physical Education professional´s identity, realizing that, yes, we are the professionals who understand the human movements, but inside a holistic perspective, concerned about men development in all their potentialities, as an unique and indivisible being, and in this way contribute so that the student acquires competence to an independent acting, seeking to be a critical and conscious citizen, looking for a social transformation with expectations in relation to his development in the discipline.